Demorest's Family Magazine - Demorest, William Jennings (New York: W.J. Demorest, 1883)
Demorest's Family Magazine. November 1883. : The Golden Wedding by John M. Macdonald -- Agathe De Valsuze: An Episode of the French Restoration Chapter 18-21 by M. D'Epagny -- My Thanksgiving Dinner -- Luther's Wedding Ring by Lydia M. Millard -- Vatel the cook of Chantilly -- The Marshall Family Coat-of-Arms, by One of Them -- Enid, A Saxon Maiden -- Red Apples by Sydney Dare -- Worn Out -- Her Glove by Bessie Chandler -- So Young to Die by L. A. Paul -- Sugar by R. H. C. -- Cousin Ebenezer by Helen Whitney Clark -- How We Live in New York: Keeping a Boarding House -- The Young Ladies of Clyde Discuss Wedding Presents by Mary C. Hungerford -- If by Mary Torrence -- By the Wood by Mary M. Bowen -- Court of a Temple of Apes at Benares, India -- Success: A Story in Two Parts -- Social Duties by Veni Vidi -- Prodigal Son -- Home Art and Home Comfort -- Janet's Love -- What Women Are Doing -- Work Bag -- Shaving Case -- The World's Progress: Our Great Railway System, Postal Matters, About Low Prices, The Church and the Stage, World Convulsions, A Wonderful Mountain Railroad, Shakespeare's Bones, The Working People and the Government, The Third Greatest Diamond, Polar Explorations, An Unostentatious French Ruler, A Wonderful Street, America and France Contrasted, A New Empire, reducing the Armies, Do we Want Cuba?, The Vatican and Modern Research, Church Property in Gin Palaces, Religious Tendencies, Progress of Aestheticism, A New Planet, and Marriage Becoming Popular -- Kitchen: Thanksgiving Dinners -- Scientific -- Diamonds of Thought -- Spice Box -- Mirror of Fashions: Review of Fashions. - November -- Paris Fashions by M. T. K. -- Illustrated Designs -- Fashionable Millinery -- Armina Polonaise -- Lakme Redingote -- Winter Hats and Bonnets -- Evening Toilets -- Out-Door Wraps -- Our "What to Wear" for the Autumn and Winter of 1883-1884 -- Greville Raglan -- Walking Costumes -- Finette Jacket -- "Nonpareil" Velveteen -- The Winter Colors -- Our "Portfolio of Fashions" for the Autumn and Winter of 1883-1884 -- Children's Fall and Winter Fashions -- Misses' Costumes -- Ladies' Club -- Review of New Publications -- A Beautiful Oil Painting -- Demorest's Illustrated Monthly Magazine: Binding of Volume XIX -- "Acadia" Velveteen -- Demorest's Monthly: The Best Medium for Advertisements
Demorest's New York Illustrated News Mme.; Demorest's Quarterly Mirror of Fashions
Missing pages cover page - 2. Digitized from original print, Valdosta State University Archives and Special Collections, February 25, 2019.
Keywords: Periodicals; Poetry; Women's History; Illustrated Periodicals; Art; Stories; Fashion